Recovery as an "Act of rebellion": a qualitative study examining feminism as a motivating factor in eating disorder recovery. Issue 3 (3rd May 2020) - Venturo-Conerly, Katherine; Wasil, Akash; Shingleton, Rebecca; Weisz, John
ABSTRACT: Patients with eating disorders (EDs) often feel ambivalent about recovery, and motivation-enhancement interventions are ineffective for many patients. Identifying new targets for motivational interventions may be particularly valuable. We interviewed 13 recovered ED patients to identify factors that motivated recovery, applying thematic analysis to identify central themes. Here we discuss exploratory findings about one theme from these interviews: the role of feminist ideas in ED recovery. Forty-six percent ( n = 6) of our participants reported that feminist themes helped them recover. Participants described understanding harmful cultural forces (e.g., weight-related stigma), developing strategies to fight these forces (e.g., challenging stigmatizing language), engaging with feminist texts, hearing about feminist ideas from clinicians, and forming relationships with female role models. Interestingly, participants did not all refer to their experiences as "feminist, " and one rejected the label. Our exploratory findings indicate that feminist ideas can motivate ED recovery, suggesting directions for future research.